The significance of human resource competence development in enhancing the income of Silk Craftsmen's SMEs - Mas'ud, Anis Anshari (Universitas Sulawesi Barat, 2023)
Competence development outlines the fundamental knowledge and work standards that must be possessed by a Mandar silk weaver to successfully increase their income. Hence, this research aims to investigate how human resource competence development can influence the income of Silk Craftsmen's SMEs in the West Sulawesi province. This research adopts a quantitative approach, collecting data through questionnaire distribution to research participants. The research is conducted in the West Sulawesi province, Indonesia, with a population of 65 Silk Craftsmen SMEs as respondents. The results of this study indicate that (1) employee skills significantly impact SME income, and (2) the government's role significantly affects SME income. The findings from this research make a significant contribution to Silk Craftsmen's SMEs by preparing them to implement sustainable human resource development